Nomadic Computing for Big Data Analytics. - Yu, Hsiang-Fu; Hsieh, Cho-Jui; Yun, Hyokun; Vishwanathan, S.V.N.; Dhillon, Inderjit (Computer (00189162), 2016)
Analyzing the massive datasets of today's applications will require scalable and sophisticated machine-learning methods. NOMAD, a novel nomadic framework, combines two common approaches: stochastic optimization and distributed computing.